اثر استخدام أسلوب التضمين في بعض القدرات البدنية والمهارية بكرة القدم لطلاب كلية التربية البدنية وعلوم الرياضة - نبيل عبد الوهاب العزاوي; سعد عامر اسماعيل (الرياضة المعاصرة)
A search on the four-door broken down as follows 1. A search on the simple introduction about the game of football and the research problem and objectives of the research and which (to identify the effect of using the style of inclusion in the development of capabilities physical and skill in the studied material soccer among Students in the first phase) and also the imposition of search (there with semantic statistical differences in the tribal tests and a posteriori the research sample in a lesson of football material Physical Education and Sports Science) also included a sample search on the (33) students out of 125 students represents researcher proportion of the amount of 26.4% of the original research community. 2. ensure that the door presentation of the results of statistical processing using a set of tables, and then analyzed and discussed in a scientific manner accurate and supported by scientific sources through this discussion and then to reach the goals of the research and verification of the hypothesis. 3. included the conclusions of which (proven effectiveness of using style modulated (containment) among a sample search members in the development of all abilities physical and skill to study the substance of football in the Faculty of Physical Education and Sports Science) and the recommendations of them (use the style modulated (containment) because of its positive impact in the development of some of the physical and skill capabilities to study the substance of football at the College of Physical Education and Sports Science and all grades).